Application of Models for Occupational Health Risk Assessment to a Resin Anchorage Production Workshop. (October 2019) - Qu, Wei; Feng, Bin; Zhang, Limei; Zhang, Haidong; Zhang, Pu; Wang, Hui; Lin, Geng; Wang, Rui
Abstract: Objective to take the occupational health risk assessment in a resin anchorage production workshop by three models for occupational health risk assessment, and explore a suitable risk assessment model for this kind of production unit. Methods the occupational health status and main chemical hazard factors of a resin anchorage production workshop were investigated. Qualitative risk assessment and semi-quantitative risk assessment (contact limit ratio method and comprehensive index method) were used for risk assessment, and the results were compared and analysed. Results Comparing with comprehensive index method, the evaluation result of qualitative risk assessment and contact ratio method were closer to each other, but there was a big difference between the two methods in the determination of phthalic anhydride. Conclusion the three risk assessment methods had their own merits and demerits, the evaluation results were also different. The semi-quantitative risk assessment-contact limit ratio method is more suitable for the occupational risk assessment in resin anchorage production workshop.